2022
DOI: 10.3390/jcm11175008
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Idiopathic Pulmonary Fibrosis and Obstructive Sleep Apnea: A Systematic Review and Meta-Analysis

Abstract: The prevalence of obstructive sleep apnea (OSA) has greatly increased in recent years. Recent data suggest that severe and moderate forms of OSA affect between 6 and 17% of adults in the general population. Many papers are reporting the significantly increased prevalence of OSA in patients suffering from fibrotic diseases, including idiopathic pulmonary fibrosis (IPF). Therefore, we performed a systematic review and meta-analysis regarding the dependency between IPF and OSA. Due to the lack of papers focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Some findings of prospective studies, including ours, on the prevalence of OSA in IPF and ILD populations are presented in Table 4 [ 15 , 16 , 18 , 22 28 , 30 , 32 37 ]. This search was not systematic, but includes all the studies (with sample size > ten subjects) reported in a recent systematic review on the topic [ 47 ]. Differences between these studies may be due to variations in age, sex, BMI, treatment, disease severity of populations, and methods.…”
Section: Discussionmentioning
confidence: 99%
“…Some findings of prospective studies, including ours, on the prevalence of OSA in IPF and ILD populations are presented in Table 4 [ 15 , 16 , 18 , 22 28 , 30 , 32 37 ]. This search was not systematic, but includes all the studies (with sample size > ten subjects) reported in a recent systematic review on the topic [ 47 ]. Differences between these studies may be due to variations in age, sex, BMI, treatment, disease severity of populations, and methods.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive sleep apnea has an increased prevalence in idiopathic PF [ 207 , 208 ] and leads to additional difficulties such as cognitive impairment [ 209 ]. Sleep apnea may promote fibrotic mechanisms [ 210 ].…”
Section: Sleep Apnea and Pulmonary Fibrosismentioning
confidence: 99%
“…Many factors affect its expression, including age, sex, ethnicity, bodily characteristics, comorbidities and sleep posture, as well as sleep stage, all of which collectively contribute to defining the endotypic and phenotypic features of OSA. and the features of respiratory events according to sleep stages [10]. The scope of this review is to examine the evidence underpinning the assertion that REM OSA may constitute a different phenotype in the heterogeneous constellation of OSA.…”
Section: Introductionmentioning
confidence: 99%